Efficacy Comparison of Ventriculoperitoneal Shunt and Endoscopic Third Ventriculostomy as Treatment of Hydrocephalus in Children in Developing Countries: A Meta-Analysis - Rasyid, Fahmi; Mouza, Abdurrahman (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Introduction: In Indonesia, cases of hydrocephalus in children are found in 40% to 50% of medical visits or neurosurgical operations. Endoscopic third ventriculostomy was one of choices for treat the patient but efficacy and effects still unknown. Purpose of this study is to broadly assess the outcome of treatments and review evidence that one treatment may have greater efficacy than another. Method: Researchers develop PICO questions. Demographic information, detailed methods, interventions, and results were extracted from the selected manuscripts. Of the 122 articles identified using optimized search parameters, 52 were withdrawn for full-text review. In total, 6 articles were accepted for inclusion in the evidentiary table and 8 were excluded for various reasons. Result: The tabulated evidence provides sufficient data to allow our evaluation of the CSF versus ETV shunt. Conclusion: CSF shunt and endoscopic third ventriculostomy (ETV) are options in the management of hydrocephalus in children